Circumventing colistin resistance by combining colistin and antimicrobial peptides to kill colistin-resistant and multidrug-resistant Gram-negative bacteria. (September 2020) - Witherell, Kaitlin S.; Price, Jason; Bandaranayake, Ashok D.; Olson, James; Call, Douglas R.
Highlights: Peptide–colistin combinations restore colistin susceptibility in mcr bacteria. Peptide–colistin combinations effectively kill multidrug-resistant bacteria. Colistin and two peptides at low concentrations kill four bacterial species. Colistin and MSI-78 alone cause red blood cell (RBC) haemolysis; peptide OTD-244 does not. At relevant concentrations, peptide–colistin combinations do not cause RBC haemolysis. Abstract: Objectives: Colistin is a 'last-line' antibiotic used to treat multidrug-resistant Gram-negative bacteria, but colistin resistance has emerged. Colistin normally binds to the lipid A moiety on the bacterial outer membrane, where it then destroys the bacterial membrane. Mobilize colistin resistance (MCR, encoded by mcr-1 and others) is a phosphoethanolamine transferase that modifies lipid A, preventing colistin binding. We hypothesized that combining pore-forming AMPs and colistin will circumvent this mechanism and reduce the minimum inhibitory concentration (MIC) of colistin for both colistin- and multidrug-resistant Gram-negative bacteria. Methods: In vitro cultures were incubated for 18 h after combining bacteria ( Escherichia coli, Klebsiella pneumoniae, Acinetobacter baumannii and Pseudomonas aeruginosa ) with serially diluted colistin and a fixed concentration of peptide MSI-78 or OTD-244. Results: When combined with either peptide, the colistin MIC decreased more than 4-fold for 88% of all tested isolates ( n = 17; range, 4–64-fold reduction) and for 75% of colistin-resistant isolates ( n = 8; range, 4–64-fold reduction). The concentrations used had no effect on red blood cells based on a conventional haemolysis assay. Conclusions: These findings are consistent with two membrane-damaging compounds having an additive effect on bacterial killing. Combining antimicrobial peptides with colistin is a promising strategy for bypassing MCR-mediated colistin resistance, but also for improving the susceptibility of other Gram-negative bacteria while potentially reducing the therapeutic concentration of colistin needed to treat infections.